Validation of the German version of the Short Health Scale: a brief, valid and reliable instrument to assess health-related quality of life in German-speaking patients with inflammatory bowel diseases = Validierung der deutschen Version der Short Health Scale : ein kurzes und zuverlässiges Instrument zur Beurteilung der gesundheitsbezogenen Lebensqualität bei Patient:innen mit chronisch-entzündlichen Darmerkrankungen - Demmer, Sina; Kleindienst, Nikolaus; Hjortswang, Henrik; Thomann, Philipp; Ebert, Matthias; Reindl, Wolfgang; Thomann, Anne K. (Zeitschrift für Gastroenterologie, 2023)
Background: Health-related quality of life (hrQoL) may be the most important patient-reported outcome for patients with chronic disorders. The Short Health Scale (SHS) is a brief four-item instrument to assess hrQoL in patients with bowel disorders. This study examined the validity, reliability and sensitivity of the German translation of the SHS in a cohort of outpatients with inflammatory bowel diseases (IBD). Methods: The study was preregistered in April 2021 (https://doi.org/10.17605/OSF.IO/S82D9). Outpatients with IBD (n=225) in different stages of disease activity (as determined by the Harvey-Bradshaw index or partial Mayo score) completed the German SHS and the short Inflammatory Bowel Disease Questionnaire (sIBDQ) as an established measure of hrQoL to examine the convergent validity. To assess reliability, a subset of patients (n=30) in remission completed the same questionnaires after 4-8 weeks. Sensitivity to change was established from questionnaires of patients with either decreased (n=15) or increased (n=16) disease activity after 3-6 months. Results: The internal consistency of the German SHS was high (Cronbach’s α=0.860). SHS total scores correlated strongly with sIBDQ scores (ρ=-0.760, p<0.001) and disease activity (ρ=0.590, p<0.001). Retest reliability was high (ρ=0.695, p<0.001). Sensitivity to change was statistically significant for patients with decreased (p=0.013) but not increased (p=0.134) disease activity. Conclusion: The German version of the SHS is a valid and reliable tool to measure hrQoL in persons with IBD.
Gesehen am 26.01.2024